Academic Writing in English in the Structure of Higher Education in Russia - E. I. Shpit; V. N. Kurovskiy (Moscow Polytechnic University, 2020)
Intensification of research work at engineering universities of Russian Federation leads to the increase of publication activity of graduate and PhD students in high-impact English language journals. However, the level of academic writing skills still remains rather low. On one hand, it results from the fact that the majority of applicants to engineering institutions have only basic knowledge of a foreign language. On the other hand, the curriculums of most Russian universities do not include developing academic writing skills as a stand-alone discipline or a part of the "Foreign Language" discipline. This paper aims at considering the main constituents of academic writing in a foreign language, such as the current state policy in higher education, the content of academic writing for engineering specialties, the publication process participants, the available resources for developing and improving the required skills in the realities of university language education; as well as identifying the external factors which create favorable conditions for developing academic writing skills of engineering students.